The Role of Physical Education in Improving the Health and Fitness of Elementary School Students - Samsidar, Samsidar (Journal of Salutare, 2025)
Physical education has a significant contribution to improving the health and fitness of elementary school students. Through structured and enjoyable physical activities, students not only develop motor skills, but also improve endurance, flexibility, and overall physical fitness. This study aims to analyze how physical education can affect health and fitness aspects in elementary school-age students through a qualitative approach. Data were obtained from indepth interviews with physical education teachers, observations of physical education learning activities in three elementary schools, and group discussions with students. The results show that a well-designed physical education program can foster awareness of the importance of an active and healthy lifestyle from an early age. In addition, physical education plays a role in forming healthy living habits, reducing the risk of obesity, and improving students' mental and social conditions. Obstacles such as limited facilities and minimal training for teachers are still major challenges. Therefore, improving the quality of physical education in elementary schools is urgent in order to create a healthy and fit generation, both physically and mentally.